Essential Inputs and Unbounded Output: An Alternative Characterization of the Neoclassical Production Function - Andreas Irmen; Alfred Maussner (Center for Economic Studies and ifo Institute (CESifo), 2014)
The Inada (1963) conditions constitute a defining property of the neoclassical production function with capital and labor as arguments. Are these conditions justifiable on economic grounds? Yes, they are: we show that a production function with positive, yet diminishing marginal products and constant returns to scale satisfies the Inada conditions if i) both inputs are essential and ii) an unbounded quantity of either input leads to unbounded output. This allows for an alternative characterization of the neoclassical production function that altogether dispenses with the Inada conditions. Moreover, we establish that the marginal product of capital vanishes as capital goes to infinity if labor is an essential input. Given the intuitive appeal of the latter feature, we conclude that the neoclassical growth model is a theory of eventual stagnation.
Keywords: E10; O10; O40; 330; neoclassical growth model; capital accumulation; stagnation; Inada conditions